Caring for older patients with cancer during the COVID-19 pandemic: a Young International Society of Geriatric Oncology (SIOG) global perspective - Desideri, Isacco; Neuendorff, Nina Rosa (Journal of geriatric oncology, 2020)
The ongoing coronavirus disease 2019 (COVID-19) pandemic has affected millions of people in over 180 territories, causing a significant impact on healthcare systems globally. Older adults, as well as people living with cancer, appear to be particularly vulnerable to COVID-19 related morbidity and mortality, which means that older adults with cancer are an especially high-risk population. This has led to significant changes in the way geriatric oncologists provide care to older patients, including the implementation of novel methods for clinical visits, interruptions or delays in procedures, and modification of therapeutic strategies, both in the curative and palliative settings. In this manuscript, we provide a global overview of the perspectives of geriatric oncology providers from countries across Europe, America, and Asia, regarding the adaptive strategies utilized to continue providing high quality care for older patients with cancer during the COVID-19 pandemic. Through these perspectives, we attempt to show that, although each country and setting has specific issues, we all face similar challenges when providing care for our older patients with cancer during these difficult times.
Gesehen am 22.10.2021